2014
DOI: 10.3389/fnagi.2014.00198
|View full text |Cite
|
Sign up to set email alerts
|

Subtype and Regional-Specific Neuroinflammation in Sporadic Creutzfeldt–Jakob Disease

Abstract: The present study identifies deregulated cytokines and mediators of the immune response in the frontal cortex and cerebellum of sporadic Creutzfeldt–Jakob disease (sCJD) MM1 and VV2 subtypes compared to age-matched controls. Deregulated genes include pro- and anti-inflammatory cytokines, toll-like receptors, colony stimulating factors, cathepsins, members of the complement system, and members of the integrin and CTL/CTLD family with particular regional and sCJD subtype patterns. Analysis of cytokines and media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
73
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 58 publications
10
73
0
Order By: Relevance
“…Recent studies revealed the distinct subtypes 0 neuropathology being the possible explanation for elevated CSF markers [20,21]. The regional specific manner of inflammatory markers between the VV1 and VV2 subtype might contribute to the different S100B CSF profile [22]. The time of sampling influenced the CSF protein levels rising in later stages of disease especially for tau, NSE and S100B (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed the distinct subtypes 0 neuropathology being the possible explanation for elevated CSF markers [20,21]. The regional specific manner of inflammatory markers between the VV1 and VV2 subtype might contribute to the different S100B CSF profile [22]. The time of sampling influenced the CSF protein levels rising in later stages of disease especially for tau, NSE and S100B (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence for microglial activation and neuroinflammation with increased expression of microglial markers in CJD 26–28 . In addition, Llorens et al has found that there is regional variation in microglia activation depending on molecular subtype in sporadic CJD 29 . An alternative explanation for limbic and mesolimbic hypermetabolism was considered because hypermetabolism has been reported in other neurological disorders, such as limbic encephalitis 30 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that marked modification of the profile of gene expression of cytokines and molecules linked with the inflammatory response occurs in the cerebral cortex and other brain regions of mice with age. This happens in normal aging and also in transgenic mice including APP/PS1, P301S-MAPT and S49P-Syracuse human neuroserpin (S49P-Syracuse), and in CJD-induced prionopathy in murine PrP-null mice expressing human PrP, which are models of human β-amyloidopathy reminiscent of Alzheimer disease, familial frontotemporal degeneration-tauopathy (FTLD-tau), neuroserpinopathy and Creutzfeldt-Jakob disease, respectively [3336]. This pattern is repeated in our study as C3ar1 , C4b , Csf3r , Tlr4 , Ccl4, Ccl6 , CxCl10 , Il1b, Il6 , Tnfα, Il10ra and Il10rb mRNA expression levels increase and C1ql1 levels significantly decrease in WT, Epm2a −/− and Epm2b −/− mice aged 12 months when compared with mice aged 16 days.…”
Section: Discussionmentioning
confidence: 99%